2023
DOI: 10.3390/vaccines11020222
|View full text |Cite
|
Sign up to set email alerts
|

Midwives’ Knowledge, Attitudes, and Practice Regarding COVID-19 Vaccination for Pregnant Women: A Nationwide Web-Based Survey in Italy

Abstract: This cross-sectional survey investigated the knowledge, attitudes, and practices concerning the COVID-19 vaccination for pregnant women among midwives in Italy and the associated factors. Midwives with at least five years of midwifery education and who had received information about the COVID-19 vaccination from official government organizations or scientific journals were more likely to know in which trimester this vaccine can be administered. A higher perceived utility of this vaccination was observed among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…This would suggest that those with co-morbidities view themselves at risk of acquiring COVID-19 infection and complications. This was echoed in the study by Miraglia et al, where participants with at least one chronic medical condition perceived themselves at greater risk for severe infection of COVID-19, and therefore were more likely to receive a COVID-19 second booster dose [32]. Contrastingly, our study also illustrated that those with comorbidities were also concerned about possible adverse effects of the vaccine on their chronic disease state and potential interactions with their medication.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…This would suggest that those with co-morbidities view themselves at risk of acquiring COVID-19 infection and complications. This was echoed in the study by Miraglia et al, where participants with at least one chronic medical condition perceived themselves at greater risk for severe infection of COVID-19, and therefore were more likely to receive a COVID-19 second booster dose [32]. Contrastingly, our study also illustrated that those with comorbidities were also concerned about possible adverse effects of the vaccine on their chronic disease state and potential interactions with their medication.…”
Section: Discussionsupporting
confidence: 43%
“…However, these findings are contradictory to a study conducted in Italy that investigated the reasons for receiving a second COVID-19 booster in adults and people with chronic medical conditions. That study revealed that younger participants decided to receive the second booster dose due to their risk of acquiring the disease and thereby transmitting it to others [32]. Contradictory findings across the countries could be explained by differing perceptions of vulnerability between the geographical populations.…”
Section: Discussionmentioning
confidence: 97%
“…It is known that parents mostly receive information regarding vaccination from healthcare professionals ( Gellin, Maibach & Marcuse, 2000 ). In a study evaluating the knowledge, attitudes, and practices of midwives regarding COVID-19 vaccination, it was reported that only 51.9% of midwives routinely provided information about COVID-19 vaccination to pregnant women, and obtaining information from official government organizations or scientific journals had a positive impact on midwives’ practices ( Miraglia del Giudice et al, 2023 ). In this regard, healthcare professionals, who serve as a source of information, should also be knowledgeable about vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review also synthetized scientific information to support communication strategies specific to vaccine-hesitant populations [38] . In addition, information regarding the second booster dose, derived from scientific journals, has positively influenced vaccine acceptance within specific population, including special groups such as health care workers [39] , [40] . Among measures undertaken to address vaccine hesitancy in NHs, some institutions mandated COVID-19 vaccination, as this has already been shown to be effective for influenza vaccination [41] , [42] .…”
Section: Discussionmentioning
confidence: 99%